The Methods of Construction in Schrödinger’s "Mitteilungen" - Hanzel, Igor (Filozofia Nauki, 2019)
The paper reconstructs the methods used by Schrödinger in the construction of wave mechanics as given in his four Mitteilungen. These methods are described from the point of view of modern philosophy of science, with a focus on the relationships between scientific theories and on the reconstruction of the structure of scientific laws and the relations between scientific laws. After reconstructing the derivation of the first equation in Mitteilung 1, it analyzes the methodology of the optical-mechanical analogy in Mitteilung 2 and reconstructs the two heuristic pathways that led to the construction of wave equations as the basis of wave mechanics in the first two Mitteilungen. Finally, it addresses the methods of generalization, application, and explanation by which the second, third, and fourth Mitteilungen are constructed.